Pemetaan sebaran fasilitas umum di Desa Haruru menggunakan teknologi drone - Dion Dollan Awayal; Alexander Yosep Elake; Pieldrie Nanlohy (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2026)
Mapping the distribution of public facilities is an important step in sustainable village development planning. Currently, Haruru Village lacks a spatial database or digital maps of its public facilities. This study aims to map the distribution of public facilities in Haruru Village using drone technology to produce accurate, up-to-date spatial data and maps. The research method consists of three stages: pre-field, field, and post-field. Data acquisition was conducted using a DJI Mavic 2 Pro drone, which provided primary data, while secondary data was sourced from RBI maps. Data processing involved image stitching using Agisoft Metashape Professional to create high-resolution orthomosaics, which were then analyzed and mapped using ArcGIS. The research results show that the spatial resolution of the drone imagery is 3.6 cm/pix, supporting mapping at a scale of 1:1000. Several general facilities were identified, including government facilities, two religious facilities, one health facility, three sports facilities, four educational facilities, residential areas, and mangrove forest areas. Additionally, there are irrigation networks and village roads. The availability of this data positions Haruru Village as a pioneer in village infrastructure development through drone mapping technology.